1992
DOI: 10.1021/bi00157a018
|View full text |Cite
|
Sign up to set email alerts
|

Subunit complementation of thymidylate synthase

Abstract: Each of the two active sites of thymidylate synthase contains amino acid residues contributed by the other subunit. For example, Arg-178 of one monomer binds the phosphate group of the substrate dUMP in the active site of the other monomer [Hardy et al. (1987) Science 235, 448-455]. Inactive mutants of such residues should combine with subunits of other inactive mutants to form heterodimeric hybrids with one functional active site. In vivo and in vitro approaches were used to test this hypothesis. In vivo comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
21
0

Year Published

1993
1993
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 23 publications
(23 reference statements)
4
21
0
Order By: Relevance
“…The greater activity seen experimentally can be attributed to the 5% of ASL activity exhibited by the D87G homotetramer. This type of complementation, the reconstruction of wild-type active sites, has also been observed in another member of the superfamily, adenylosuccinate lyase [104], as well as in the homotrimeric enzyme aspartate transcarbamoylase [123], and homodimeric proteins glutathione reductase [124], thymidylate synthase [125], mercuric reductase [126], and ribulose bisphosphate carboxylase/oxygenase [127]. The reconstruction of active sites clearly explains the complementation event observed between the Q286R and D87G mutations of ASL.…”
Section: Intragenic Complementationsupporting
confidence: 55%
“…The greater activity seen experimentally can be attributed to the 5% of ASL activity exhibited by the D87G homotetramer. This type of complementation, the reconstruction of wild-type active sites, has also been observed in another member of the superfamily, adenylosuccinate lyase [104], as well as in the homotrimeric enzyme aspartate transcarbamoylase [123], and homodimeric proteins glutathione reductase [124], thymidylate synthase [125], mercuric reductase [126], and ribulose bisphosphate carboxylase/oxygenase [127]. The reconstruction of active sites clearly explains the complementation event observed between the Q286R and D87G mutations of ASL.…”
Section: Intragenic Complementationsupporting
confidence: 55%
“…The three-dimensional structure of human ASL described herein has enabled us to study the concept of intragenic complementation found in certain ASL-deficient strains and provides experimental proof of Crick and Orgel's initial hypothesis of intragenic complementation (17). Evidence for complementation according to the scheme of statistical regeneration of wild-type active sites also has been observed in vitro for the homodimeric proteins thymidylate synthase (18), ribulose-bisphosphate carboxylase͞oxygenase (19), glutathione reductase (20), and mercuric reductase (21) and the homotrimeric enzyme aspartate transcarbamoylase (22). As intragenic complementation has been implicated in other diseases involving mutations in homomultimeric proteins such as propionic acidemia (23,24) and methylmalonic aciduria (25), a logical extension to heteromultimeric proteins also may apply, making intragenic complementation a much overlooked source of phenotypic and biochemical variation in genetic disease.…”
supporting
confidence: 58%
“…Several groups achieved separation of heterodimers (hybrid dimers) from both parental homodimers using N-or C-terminal tags of six histidines (His-tag), FLAG, polyarginine (Arg-tail), or polyglutamate (Glu-tail) [16][17][18][19][20][21][22]. We had previously found that Arg-tailed PQQGDH-B showed increased affinity to a cation exchange column and could be effectively separated from wild-type enzyme.…”
Section: Construction Of Heterodimeric Pqqgdh-bmentioning
confidence: 99%